A Longitudinal Examination of Service Utilization and Trauma Symptoms among Young Women with Prior Foster Care and Juvenile Justice System Involvement - Franz, Daschel J. (Child Welfare, 2019)
We investigated the prediction of young adult service utilization and trauma symptoms from adverse childhood experiences (ACEs) and adolescent mental health symptoms in young women with dual child welfare and juvenile justice system involvement. A sample of 166 females (ages 13 to 17) was followed to examine the transition to young adulthood. Path models indicated that more ACEs were associated with poorer adolescent mental health. Adolescent mental health symptoms were associated with more young adult trauma symptoms and service utilization. Implications for service providers and policy-makers are discussed.